2008
DOI: 10.1007/s10787-008-8017-8
|View full text |Cite
|
Sign up to set email alerts
|

Green tea polyphenols as a natural tumour cell proteasome inhibitor

Abstract: The cancer-preventive effects of green tea and its main constituent (-)-epigallocatechin gallate [(-)-EGCG] are widely supported by results from epidemiological, cell culture, animal and clinical studies although the molecular target has not been well defined. We previously reported that ester bond-containing tea polyphenols, e. g. (-)-EGCG, and their synthetic analogs potently and specifically inhibited the proteasomal activity. Subsequently, we further demonstrated that methylation on green tea polyphenols u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 24 publications
0
34
0
1
Order By: Relevance
“…3) which are metabolites or potential metabolites of tea catechins in biomethylation [123]. It was found that the addition of a methyl group on the B- or D-ring of (−)-EGCG or (−)-ECG led to decreased proteasome inhibition and, as the number of methyl groups increased, the inhibitory potencies further decreased [124]. Metabolic O-methylation of EGCG may indeed reduce the effectiveness of EGCG as it relates to its anticancer activity [125], lending support of the human study [122].…”
Section: Tea Polyphenol Derivatives In Cancer Studiesmentioning
confidence: 99%
“…3) which are metabolites or potential metabolites of tea catechins in biomethylation [123]. It was found that the addition of a methyl group on the B- or D-ring of (−)-EGCG or (−)-ECG led to decreased proteasome inhibition and, as the number of methyl groups increased, the inhibitory potencies further decreased [124]. Metabolic O-methylation of EGCG may indeed reduce the effectiveness of EGCG as it relates to its anticancer activity [125], lending support of the human study [122].…”
Section: Tea Polyphenol Derivatives In Cancer Studiesmentioning
confidence: 99%
“…A number of studies have demonstrated the proteasome inhibitory effects of green tea polyphenol EGCG and its related analogs [110,111] and these observations led to the exploration of their potential against F-BOX family members and also for their muscle atrophy preventive mechanisms of action. This becomes especially relevant given that EGCG is capable of down-regulating SKP2 in breast cancer cell lines indicating that it can impact E-3 ubiquitin ligases [112].…”
Section: Natural Products Targeting F-box Family Proteins and Theimentioning
confidence: 99%
“…General protease activity and activity associated with a chymotrypsin-like protease from the proteasome were affected. EGCG was again one of the more effective analogues, and its known interaction with the proteasome (Lam et al, 2004;Dou et al, 2008;Dou, 2009) and the possible role of the proteasome in nematode development and oogenesis (Pispa et al, 2008) make the EGCG-proteasome interaction of continuing interest.…”
Section: Forum Article: Internal Processes O F Plant-parasitic Nematodesmentioning
confidence: 99%